Bariery społeczno-kulturowe w dostępie do edukacji dzieci w Afryce Subsaharyjskiej - Lendzion, Kinga (Wydawnictwo Naukowe UAM, 2015)
Sub-Saharan Africa is a region with the highest illiteracy and the lowest percentage of children attending primary schools. According to UNESCO in 2011, 41% of adults (over the age of 15) were illiterate. 30% of the illiterate adult population were aged between 16 and 24. Primary schools are attended by only 77% of children. As a result, Black Africa is home to more than half of the children of the world who do not access primary level education. There are many reasons that cause this situation. Apart from the insufficient number of schools, Sub-Saharan Africa is one of the poorest regions in the world, which means that children are forced to work, with an estimated one in three children starting work between the ages 5-14. However, it is Cultural Barriers that are the biggest obstacle preventing access to education in Africa. There are vast cultural differences between traditional Sub-Saharan African communities and West European civilisation. School education in Africa is not, as in Europe, the continuity of the values of family upbringing. In fact, school introduces children to an unfamiliar world and values, often contradictory to their previously held family values.
Socio-cultural Barriers in Children’s Access to Education in Sub-Saharan Africa
Keywords: education system; access to education; child labour; poverty; culture